Razvojni dejavniki v Sloveniji - ustvarjalnost in naložbe - Ravbar, Marjan (Georitem, 2009)
Global scientific literature widely deals with analysis of regional innovative systems and their contribution to economic growth. Modern theories and empirical researches indicate strong correlation between the technical progress, creative human resources, toleration and capital investments. New investments are basic but not sufficient condition for balancing the developmental stimulation. Capital, linked with investment activities, natural (material) resources and human resources (work, knowledge, information) are main driving forces of the economic progress. New forms of investments today are strongly connected with population educational structure and knowledge, therefore investments do not occur everywhere, simultaneously and equally.